(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The article discusses the importance of effective pedagogical approach of teaching in primary education. Two different approaches are analyzed and presented in the article. Also, the key differences between them as well as their advantages and disadvantages are identifies throughout the article with valid examples and evidences.